The perceived influence of COVID-19 preventive measures on the profit efficiency of smallholders’ cereal marketers in Cameroon - Djomo Choumbou Raoul Fani; Ukpe Udeme Henrietta; Rayner Tabetando; Gama Emmanuel Nkwi; Siewe Francois; Godwin Anjeinu Abu; Ali Ayuba; Zoubeirou Mainassara; Opaluwa Haruna Ibrahim; Donald Denen Dzever; Obi Samuel; Bethel Fidelis Ewung (Cogent Social Sciences)
This study was carried out to analyse the perceived influence of COVID-19 preventive measures on the profit efficiency of smallholders’ cereal marketers in Cameroon. The study hypothesizes that COVID-19 preventive measures significantly influence cereal marketers’ profit efficiency. A method of sampling, involving multiple stages and random selection, was employed to choose a group of 747 cereal marketers, and was analysed via the stochastic frontier model and beta regression. Cereal marketers are aware of the COVID-19 pandemic (80%), and of the government preventive policy measures (63%). The number of days in lockdown, the costs of hand sanitizer and face masks negatively influence cereal marketers’ profit efficiency while community sensitization positively influence cereal marketers’ profit efficiency. Borrowed money from friends (73%), Borrowed of money from money lenders (69%), withdrawal of savings (70%), material/financial support (37%), sell off assets to meet the daily need (73%), reduction of the quality of meals eaten (66%), and sell off reserved food to earn more money (63%) are the copying strategies used by cereal marketers. The study did not involve control groups that face different levels of exposure, and suggest that control groups could help isolate the effects of preventive measures from other external factors and provide a basis for comparison for further studies. To make preventive outbreak measures effective, price subsidies should be implemented to enable the use and access of hand sanitizer and disposable face masks, and the continuous wide broadcasting through community sensitization.